Application of industrial ecology in water utilization of coal chemical industry: A case study in Erdos, China. (1st November 2016) - Jia, Shengyong; Zhuang, Haifeng; Han, Hongjun; Wang, Fengjun
Abstract: China has been accelerating coal chemical development, more and more industries have focused on the highly efficient water utilization. The water utilization in coal chemical industry was evaluated in Erdos, China. According to the industrial ecology principles, the processes in sectors of pretreatment, desalination, wastewater treatment plant, reuse, recirculation and brine have been fully discussed. The water balance was investigated to evaluate water reuse, reaching efficiencies of 70–81%. Two major cleaner production measures based on industrial ecology have been transformed: 1, the production water of pretreatment has been mainly pumped to recirculation sector as supplement; 2, production water of reuse sector has been transferred to desalination sector. Results indicated that if the production water from reuse sector to desalination sector was sufficient, 15, 000 tons of pretreatment production water scheduled for desalination sector and cost of 730 United States Dollars have been saved daily. The driving forces for industrial ecology implementation in the industry mainly included the requirements of resource and environment, industrial policy, technical support and enterprise culture. And the present technologies of water utilization in this industry provided scientific guidance for the designs and operation of water utilization for the coal chemical industry. Graphical abstract: Highlights: Highly efficient water utilization was realized in a coal chemical industry. Water reuse efficiencies of the whole industry stayed in the scope of 70–81%. Processes of wastewater treatment plant and brine sectors are the key techniques. The industry deserved to be Green Engineering for the zero liquid discharge. This study provided scientific guidance for designs and operations for other cases.